2021
DOI: 10.2215/cjn.09190620
|View full text |Cite
|
Sign up to set email alerts
|

Variability in Culture-Negative Peritonitis Rates in Pediatric Peritoneal Dialysis Programs in the United States

Abstract: Background and objectivesInternational guidelines suggest a target culture-negative peritonitis rate of <15% among patients receiving long-term peritoneal dialysis. Through a pediatric multicenter dialysis collaborative, we identified variable rates of culture-negative peritonitis among participating centers. We sought to evaluate whether specific practices are associated with the variability in culture-negative rates between low– and high–culture-negative rate centers.Design, setting, participants, & m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Improvement science has been used successfully in decreasing peritonitis rates among children by standardizing protocols and reducing practice variation [ 2 ], and it is thus not surprising that similar methods may be used for reducing culture-negative peritonitis rates. While Davis et al reported high culture-negative peritonitis rates among surveyed centers, an association with peritoneal effluent collection and/or laboratory processing methods was not reported [ 9 ]. Based on published evidence, we hypothesized that process measures were responsible for our high rate of culture-negative peritonitis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Improvement science has been used successfully in decreasing peritonitis rates among children by standardizing protocols and reducing practice variation [ 2 ], and it is thus not surprising that similar methods may be used for reducing culture-negative peritonitis rates. While Davis et al reported high culture-negative peritonitis rates among surveyed centers, an association with peritoneal effluent collection and/or laboratory processing methods was not reported [ 9 ]. Based on published evidence, we hypothesized that process measures were responsible for our high rate of culture-negative peritonitis.…”
Section: Discussionmentioning
confidence: 99%
“…There is limited data regarding risk factors for culture-negative peritonitis, although those identified—such as culture methodology [ 6 ], dialysate culture volume [ 6 ], antibiotic use with 30 days, and collection by staff without dialysis specialty training [ 7 ]—are related to processes rather than intrinsic patient factors. The Standardizing Care to Improve Outcomes in Pediatric End Stage Kidney Disease (SCOPE) Collaborative, a collaborative of 51 North American institutions whose goal is to prevent dialysis-associated infections among pediatric chronic PD patients [ 8 ], reported an overall culture-negative peritonitis rate of 26.6%, with significant variability in culture-negative peritonitis rates and peritoneal effluent collection methods and processes among 32 surveyed centers, with our institution falling among the higher rates [ 9 ]. In order to reduce culture-negative peritonitis rates among participating centers, the SCOPE Collaborative proposed a standardized culture method process (or “bundle”) aimed to reduce culture-negative peritonitis rates [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…1 hour) are associated with more culture-negative samples and low WBC counts compared to those collected after a longer dwell time (e.g. at least 2 hours, as recommended in the ISPD Peritonitis guidelines) (1,22,23). Treatment and management of a patient with culture-negative peritonitis (no causative organism identified) is problematic and may result in the use of unnecessary or inappropriate antibiotics.…”
Section: How To Proceed With the Follow-up Pd Effluent Collection Aft...mentioning
confidence: 99%
“…at least 2 h, as recommended in the ISPD Peritonitis Guidelines). 1,22,23 Treatment and management of a patient with culture-negative peritonitis (no causative organism identified) is problematic and may result in the use of unnecessary or inappropriate antibiotics. Above all, standardisation of collection of PD effluent samples for culture and WBC count (following ISPD Peritonitis Guidelines) should result in the causative organism with sensitivities being identified more often (culture-positive peritonitis), as well as facilitating interpretation of WBC counts, thus improving management of a patient on PD with peritonitis.…”
Section: How To Proceed With the Follow-up Pd Effluent Collection Aft...mentioning
confidence: 99%
“…In this issue of CJASN, Davis et al (7) analyzed the topic of culture-negative peritonitis in 32 pediatric dialysis centers across the United States, within the framework of the SCOPE Collaborative. The study period ranged from the start of the quality initiative (October 2011) to March 2017.…”
mentioning
confidence: 99%